IDENTIFIKASI LOYALITAS MAHASISWA MEMANFAATKAN LAYANAN UPT PERPUSTAKAAN DI SEKOLAH TINGGI ILMU KESEHATAN (STIKES) HARAPAN BANGSA PURWOKERTO JUDUL INDONESIA - Istiningrum, Farida (STIE AUB Surakarta)
The purpose of this research is to examine the Effect of Service, Information Control and Library as a place to the satisfaction and loyalty of the students and to examine the effect of satisfaction to loyalty in UPT STIKES Harapan Bangsa Purwokerto. The research is in a form of survey. Data being used are primary data by collecting the samples form the students of STIKES Harapan Bangsa Purwoketo.to the number of 126 respondents. Data analysis method is tested usingvalidation test, realibility test, partial test(‘t’ test), simultaneous test (‘F’ test), ‘R’ test, and lane analysis test. The result of ‘t’ test is as follow: From ‘t’ test on the first equation, it can be conluded that Information Control has a positive and significant effect to satisfaction. It can be observed from each variable significance value < 0,05. On the other hand, the Effect of Service and Library as a place has a negative though insignificant effect to satisfaction. From ‘t’ test on the second equation, it can be conluded that satisfaction has a positive and significant effect to loyalty. It can be observed from each variable significance value < 0,05. On the other hand, the Effect of Service, Information Control and Library as a place has a positive though insignificant effect to loyalty. The result of simultaneous test (‘F’ test) together with the variable Effect of Service and Library as a place has a positive and significant effect to the satisfaction and loyalty of the students of STIKES Harapan Bangsa Purwokerto. ‘R’ square test shows that 40,6% variation of Effect Quality of Service, Information Control Quality and Library as a place Quality. The rest 59,4% is explained using other factors excluding model. Based on the test using LibQual+™ method, the quality of library service of STIKES Harapan Bangsa Purwokerto is rated satisfactory by the students with perception value of 6,58, minimum value is 5,74, ideal value is 7,77 with AG value of 0,84 and SG value of -1,19. Based on the variables, the Service Effect value on perception score is 6,45, minimum value is 5,64, ideal value is 7,67, with AG value of 0,81 and SG value of -1,22. Information of Control value on perception score is 6,36, minimum value is 5,69, ideal value is 7,77, with AG value of 0,67 and SG value of -0,40. Library as a Place gets the highest score among the others with value on perception score is 6,92, minimum value is 5,87, ideal value is 7,86, with AG value of 1,05 and SG value of -0,904. Superiority Gap (SG) score shows negative score, which means that the service quality of STIKES Harapan Bangsa Purwokerto is on minimum acceptable level.Keyword: Dimensi Effect of Service, Information Control dan Library as place